2015
DOI: 10.1101/gr.190868.115
|View full text |Cite
|
Sign up to set email alerts
|

Tandem repeat variation in human and great ape populations and its impact on gene expression divergence

Abstract: Tandem repeats (TRs) are stretches of DNA that are highly variable in length and mutate rapidly. They are thus an important source of genetic variation. This variation is highly informative for population and conservation genetics. It has also been associated with several pathological conditions and with gene expression regulation. However, genome-wide surveys of TR variation in humans and closely related species have been scarce due to technical difficulties derived from short-read technology. Here we explore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 88 publications
5
41
0
Order By: Relevance
“…Indeed, the UGUGU pentamers are highly enriched in introns, lncRNAs and intergenic RNAs, which contain many putative TDP-43-binding sequences (Polymenidou et al, 2011; Tollervey et al, 2011). Given that microsatellites within the promoters and other cis -regulatory regions can greatly increase the divergence of gene expression profiles across the great apes (Bilgin Sonay et al, 2015; Gymrek et al, 2016), microsatellites located in untranslated regions or introns may also have a physiological role for proteotoxicity as disease modifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the UGUGU pentamers are highly enriched in introns, lncRNAs and intergenic RNAs, which contain many putative TDP-43-binding sequences (Polymenidou et al, 2011; Tollervey et al, 2011). Given that microsatellites within the promoters and other cis -regulatory regions can greatly increase the divergence of gene expression profiles across the great apes (Bilgin Sonay et al, 2015; Gymrek et al, 2016), microsatellites located in untranslated regions or introns may also have a physiological role for proteotoxicity as disease modifiers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent analysis of tandem repeats between humans and NHPs found that genes containing repeats show higher expression divergence between species, including in brain samples (Bilgin Sonay et al, 2015). Repeats that are conserved in NHPs but different in human (either fixed across humans or polymorphic) show enrichment for neural-development-related categories.…”
Section: Mutations To Noncoding Regulatory Regionsmentioning
confidence: 99%
“…Sonay et al . studied STRs in both human and nonhuman great ape genomes and showed that STRs contribute significantly to the diversity and divergence of gene expression among species13181920. These findings indicate that STRs are essential elements in molecular evolution and underscore their functional potential.…”
mentioning
confidence: 85%
“…First, STRs are abundantly located in promoters across eukaryotic organisms (ranging from yeast to rodents and humans)121314 and variations in the length of a few STRs in model organisms have been associated with changes in phenotype or gene transactivation141516. Second, an increasing body of evidence suggests that STRs play important roles in molecular evolution17.…”
mentioning
confidence: 99%